Soluble tumor necrosis factor-alpha receptors in the serum of endometriosis patients. (May 2016) - Othman, Essam R.; Hornung, Daniela; Hussein, Mostafa; Abdelaal, Ibraheem I.; Sayed, Ayat A.; Fetih, Ahmed N.; Al-Hendy, Ayman
Abstract: Introduction: We examine serum levels sTNFR-I and sTNFR-II in endometriosis patients, and their role as biomarkers of endometriosis. Material and methods: Women were diagnosed with endometriosis during laparoscopy to investigate pelvic pain and/or infertility ( N  = 62). Control group included women with pelvic pain and/or infertility, whose laparoscopy showed no abnormalities ( N  = 55). Serum concentrations of sTNFR-I and sTNFR-II were measured using Bioplex Protein Array system. Non-parametric statistics were used. Results: Endometriosis patients had significantly higher levels of sTNFR-I than controls (257.46 pg/ml, IQR = 2.37–1048.92 versus 130.39 pg/ml, IQR = 0.99–361.1 respectively, P value = 0.01). For TNFR-II, difference between women with (232 pg/ml, IQR = 0.0–624.4), and women without (132.93 pg/ml, IQR = 0.0–312.81) endometriosis was not significant ( P value = 0.05). Early stage endometriosis patients had significantly higher level of sTNFR-I (559.13, IQR = 1.82–1289.86) and sTNFR-II (248.8, IQR = 0–644.65) than control women ( P value is 0.01 for TNFR-I and 0.04 for TNFR-II). Levels of sTNFR-I and sTNFR-II were comparable for advanced endometriosis and controls, and between early and advanced endometriosis. As a biomarker for all- stage endometriosis, sTNFR-I produces AUC of 0.62, sensitivity of 61%, and specificity of 47.3%, at a cutoff of 81.87 pg/ml. For early stage disease, sTNFR-I yields AUC of 0.68, sensitivity of 60.7%, specificity of 75%, at a cutoff of 351.22 pg/ml. Conclusion: sTNFR-I is significantly higher in serum of endometriosis patients than controls. As an endometriosis biomarker, sTNFR-I achieves better performance for early stage disease.